Spectroscopic Analysis of Optoelectronic Semiconductors - Jimenez, Juan; Tomm, Jens W. (Springer Series in Optical Sciences, 2016)
This book deals with standard spectroscopic techniques which can be used to analyze semiconductor samples or devices, in both, bulk, micrometer and submicrometer scale. The book aims helping experimental physicists and engineers to choose the right analytical spectroscopic technique in order to get specific information about their specific demands. For this purpose, the techniques including technical details such as apparatus and probed sample region are described. More important, also the expected outcome from experiments is provided. This involves also the link to theory, that is not subject of this book, and the link to current experimental results in the literature which are presented in a review-like style. Many special spectroscopic techniques are introduced and their relationship to the standard techniques is revealed. Thus the book works also as a type of guide or reference book for people researching in optical spectroscopy of semiconductors.